Edu-Finance Management Model in BOS Fund Management to Create Financial Well-Being - Ulfah, Maria; Thoharudin, Munawar (Dinamika Pendidikan, 2020)
The purpose of this study is to analyze the implementation of BOS fund management and to design an edu-finance management model in order to achieve school financial well-being. The research approach used was a qualitative approach. Data sources consisted of BOS fund managers and school principals. Data collection techniques included FGDs with BOS fund managers; interview; and documentation. Data analysis techniques used the Miles and Hubermans model including data reduction, data presentation and drawing conclusions and verification. The conclusion of this research is that the compilers of school financial planning and work programs are made only to fulfill administrative requirements; the implementation of financial management in the management of BOS fund is still low; in making accountability reports, many do not understand the evidence documents that must be prepared and financial management training has not been carried out in accordance with the needs. After being given edu-finance training, the BOS fund managers understand the preparation of work programs, the use of BOS fund based on a priority scale, and the preparation of accountability reports along with the files that should be prepared.